Lithium isotopic composition of reference materials of biological origin TORT-2, DORM-2, TORT-3, DORM-4, SRM-1400 and ERM-CE278k. Issue 7 (28th June 2021) - Thibon, Fanny; Weppe, Lucas; Montanes, Maryline; Telouk, Philippe; Vigier, Nathalie
Abstract : Li isotope compositions of soft tissues and bones from six international reference materials of biological origin has been characterized with MC-ICP-MS. Abstract : This study reports Li concentrations and Li isotope compositions of soft tissues and bones from six international reference materials of biological origin, i.e., lobster hepatopancreas (TORT-2 and TORT-3), dogfish muscle (DORM-2 and DORM-4), mussel tissue (ERM-CE278k), and bone ash (SRM-1400). An in-house standard of plankton material (PLK-VLFR) has also been characterized. The seven materials display Li concentrations ranging from 0.05 μg g −1 DW (for DORM-2) to 10.5 μg g −1 DW (for PLK-VLFR). The Li purification technique used for Li isotope analyses is classical, with AG-50-X12 resin. Using the MC-ICP-MS Neptune Plus for Li isotope ratio measurements, the average δ 7 Li values, based on 3 to 9 replicates for each material, are 30.98 ± 0.47‰, 19.28 ± 4.90‰, 22.64 ± 2.81‰, 29.17 ± 0.24‰, 24.17 ± 0.32‰, 14.69 ± 0.35‰, and −1.72 ± 0.48‰ for PLK-VLFR, DORM-2, TORT-2, DORM-4, TORT-3, ERM-CE278k, and SRM-1400 respectively. The long-term analytical reproducibility (∼1 year) is estimated at ±0.18‰ (2SD) based on 20 replicate analyses of the pure reference solution Li7-N above 2 ng mL −1 . It decreases at ±2.5‰ when the solutions are measured below 0.5 ng mL −1 . For the reference materials of biological origin studied here, the Li isotope ratio uncertainties always remain below ±0.5‰ (2SD) when the Li amount loaded on the column is above 2 ng. However, it increases exponentially below this limit (up to ±2.4‰ for 1 ng Li). For the material with the lowest Li concentrations, DORM-2, a standard addition method was employed to precisely measure Li isotope ratios and to better assess the corresponding accuracy and reproducibility. This method leads to a much better precision (2SD = 1.1‰ vs. 4.9‰). Overall, this study characterizes the Li isotope composition of materials of biological origin and advises to consider a lower precision when discussing δ 7 Li values of low Li materials measured without standard addition.